ANALISIS HUKUM TENTANG PROSES LITIGASI DALAM KASUS PERDATA DI INDONESIA - Meta Puspita Sari; Wina Aprillia (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research aims to analyze in depth the litigation process in civil cases in Indonesia based on a positive legal perspective. Litigation as a dispute resolution mechanism through the courts has formally regulated stages and requires a comprehensive understanding to achieve justice. This study examines the flow of the civil litigation process starting from the filing of a lawsuit, the defendant's answer, the plaintiff's replica, the defendant's duplicate, proof, to the court decision. In addition, this study also identifies potential problems and challenges that may arise in each stage of the civil litigation process in Indonesia, as well as efforts that can be made to improve the efficiency and effectiveness of civil dispute resolution through litigation. The research method used is normative legal research with a legislative approach and conceptual analysis of relevant laws and regulations and legal doctrines. The results of the study are expected to provide a better understanding of the dynamics of the civil litigation process in Indonesia and its implications for law enforcement and access to justice for the community.